INTERNET-BASED VIDEO LESSONS ON THE LEARNER'S ENGLISH PRONUNCIATION: WHAT THE RESEARCH REVEALS - Fauziah Amanda; Fuad Abdullah; Arini Nurul Hidayati; Agis Andriani; Soni Tantan Tandiana; Dewi Rosmala (English Education Department, 2023)
Pronunciation has regained its existence in the investigative attempts in the areas of TESOL, Sociolinguistics, and Intercultural Communication. This burgeoning growth has proven the importance of pronunciation teaching and learning, notable in this technology-based language learning era. However, little attention has been given to the description of how the participant learned English pronunciation through internet-based video lessons (IBVL). Hence, this study addressed the void. Avril (a senior high school student in Tasikmalaya, West Java, Indonesia) was recruited as the investigative participant. The data were collected through semi-structured interviews and analyzed with Thematic Analysis. The findings reported that she learned English pronunciation by imitating the English tutor of the MmmEnglish channel. She learned by applying three main stages, namely listening and reading, listening and repeating, and shadowing.